Sistematika dan Persentase Bab-Bab Hadis - Suwarni Suwarni; Maizuddin Maizuddin (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2018)
Sunan is a book compiled based on fiqh chapters or contains ahkam (law) traditions to be used as a reference for fiqh scholars in legal matters, such as the books of Sunan al-Nasai, Sunan Abi Dawud, Sunan al-Tirmidhi, Sunan Ibn Majah, and Sunan al-Darimi. However, there are differences in the systematics and percentages in some of these sunan books. To see this problem further, this literature review was carried out descriptively and comparatively by referring to related sources. In the book of sunan, it was found that there were some books that did not strictly use the systematics based on the fiqh chapter, as they were named the book of sunan. The systematics and percentage of hadith chapters in the Sunan book as a whole differ both in terms of the number of chapters and the number of hadith in the Sunan book. Sunan adalah kitab yang disusun berdasarkan bab-bab fikih atau berisi tentang hadis-hadis ahkam (hukum) untuk dipakai sebagai referensi ulama fikih dalam istinbat hukum, seperti kitab Sunan al-Nasai, Sunan Abi Dawud, Sunan al-Tirmidzi, Sunan Ibnu Majah, dan Sunan al-Darimi. Namun, ada perbedaan dalam sistematika dan persentase pada beberapa kitab sunan tersebut. Untuk melihat permasalahan ini lebih lanjut, kajian kepustakaan ini dilakukan secara deskriptif dan komparatif dengan merujuk pada sumber-sumber terkait. Dalam kitab sunan, ditemukan ada sebagian kitab yang tidak secara ketat menggunakan sistematika berdasarkan bab fikih, sebagaimana penamaannya sebagai kitab sunan. Sistematika dan persentase bab-bab hadis dalam kitab sunan secara keseluruhannya berbeda-beda baik dari segi jumlah bab maupun jumlah hadis dalam kitab sunan tersebut.